2012 Joint Working IEEE/IFIP Conference on Software Architecture and European Conference on Software Architecture 2012
DOI: 10.1109/wicsa-ecsa.212.18
|View full text |Cite
|
Sign up to set email alerts
|

Forces on Architecture Decisions - A Viewpoint

Abstract: Abstract-In this paper, the notion of forces as influences upon architecture decisions is introduced. To facilitate the documentation of forces as a part of architecture descriptions, we specify a decision forces viewpoint, which extends our existing framework for architecture decisions, following the conventions of the international architecture description standard ISO/IEC/IEEE 42010. The applicability of the viewpoint was validated in three case studies, in which senior software engineering students used it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…In (Van Heesch et al, 2012a) decision views based on the conventions of ISO/IEC/IEEE 42010 are described to support documentation. In (Van Heesch et al, 2012b) the system context of decisions is defined by a set of forces affecting the problem, i.e., any aspect of the problem considered when solving it. In (Manteuffel et al, 2016) the implementation of a tool for documenting decisions is presented.…”
Section: Related Workmentioning
confidence: 99%
“…In (Van Heesch et al, 2012a) decision views based on the conventions of ISO/IEC/IEEE 42010 are described to support documentation. In (Van Heesch et al, 2012b) the system context of decisions is defined by a set of forces affecting the problem, i.e., any aspect of the problem considered when solving it. In (Manteuffel et al, 2016) the implementation of a tool for documenting decisions is presented.…”
Section: Related Workmentioning
confidence: 99%
“…In the literature, these decisions are often referred to as architecture decisions (van Heesch et al, 2012b;Ven et al, 2006). The architecture decisions together with the corresponding design constitute the software architecture of a system.…”
Section: Architecture Decisionsmentioning
confidence: 99%
“…Here, a force is "any aspect of an architectural problem arising in the system or its environment (operational, development, business, organizational, political, economic, legal, regulatory, ecological, social, etc. ), to be considered when choosing among the available decision alternatives" (van Heesch et al, 2012b). Forces are manifold, and they arise from many different sources.…”
Section: Decision Forcesmentioning
confidence: 99%
“…But it is hard to decide for the right solution for the problem to solve, which might result in selecting inapplicable architectural solutions and thus increasing the risk of fail. There are multiple factors like uncertainty about advantages and disadvantages of solutions, costs, and implications of a solution, which influence the decision, also known as forces [22]. However, a survey of practitioners conducted by Tang et al revealed that design constraints are one of the most important factors in design rationale [17].…”
Section: Introductionmentioning
confidence: 99%